Establishment of a Novel Mouse Model of Coronary Microembolization - Cao, Yuan-Yuan (Chin Med J (Engl), 2016)
BACKGROUND: Coronary microembolization (CME) has been frequently seen in acute coronary syndromes and percutaneous coronary intervention. Small animal models are required for further studies of CME related to severe prognosis. This study aimed to explore a new mouse model of CME. METHODS: The mouse model of CME was established by injecting polystyrene microspheres into the left ventricular chamber during 15-s occlusion of the ascending aorta. Based on the average diameter and dosage used, 30 C57BL/6 male mice were randomly divided into five groups (n = 6 in each): 9 μm/500,000, 9 μm/800,000, 17 μm/200,000, 17 μm/500,000, and sham groups. The postoperative survival and performance of the mice were recorded. The mice were sacrificed 3 or 10 days after the surgery. The heart tissues were harvested for hematoxylin and eosin staining and Masson trichrome staining to compare the extent of inflammatory cellular infiltration and fibrin deposition among groups and for scanning transmission electron microscopic examinations to see the ultrastructural changes after CME. RESULTS: Survival analysis demonstrated that the cumulative survival rate of the 17 μm/500,000 group was significantly lower than that of the sham group (0/6 vs. 6/6, P = 0.001). The cumulative survival rate of the 17 μm/200,000 group was lower than those of the sham and 9 μm groups with no statistical difference (cumulative survival rate of the 17 μm/200,000, 9 μm/800,000, 9 μm/500,000, and sham groups was 4/6, 5/6, 6/6, and 6/6, respectively). The pathological alterations were similar between the 9 μm/500,000 and 9 μm/800,000 groups. The extent of inflammatory cellular infiltration and fibrin deposition was more severe in the 17 μm/200,000 group than in the 9 μm/500,000 and 9 μm/800,000 groups 3 and 10 days after the surgery. Scanning transmission electron microscopic examinations revealed platelet aggregation and adhesion, microthrombi formation, and changes in cardiomyocytes. CONCLUSION: The injection of 500,000 polystyrene microspheres at an average diameter of 9 μm is proved to be appropriate for the mouse model of CME based on the general conditions, postoperative survival rates, and pathological changes.